The Effect of Profitability, Leverage, Institutional Ownership, and Audit Quality on Tax Avoidance: Study on Mining Companies Listed on BEI Period 2016-2020 - Ichwantoro, Muhammad Rizky; Widiastuti, Sri Wahyuni; Hastuti, Sri (AIBPM Publisher, 2022)
This research aims to obtain empirical evidence regarding the effect of profitability, leverage, institutional ownership, and audit quality on tax avoidance. The measurement of tax avoidance in this study uses the Effective Tax Rate method. This research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The number of observations was 47 research samples obtained by purposive sampling technique. The analytical technique used in this research is multiple linear regression analysis. The results of the analysis show that institutional ownership and audit quality have an effect on tax avoidance, while profitability and leverage variables have no effect on tax avoidance.